Waqf management reform: A pathway to alleviate poverty within Muslim societies / Mohd Owais and Jawwad Ali - Owais, Mohd (Universiti Teknologi MARA Selangor, 2023)
Poverty has been a persistent challenge throughout human history and remains a significant issue globally, especially in developing countries. This paper aims to explore the potential impact of Waqf (Islamic endowment) in alleviating poverty and promoting socioeconomic development within the Muslim community. As an Islamic economic tool, Waqf was introduced to improve the standard of living and support individuals in need. Using a socio-legal paradigm, this paper qualitatively analyzes the available literature to highlight and discuss the role that Waqf plays in poverty reduction and improving people's quality of life. The research reveals that the Waqf institution has significant financial and infrastructural resources that can play a crucial role in reducing poverty in the Muslim community. Historically, Waqf has been used to provide revenue, support social welfare and economic development, and enhance infrastructure over extended periods. However, the management of Waqf institutions in Muslim societies requires improvement to facilitate further progress. This paper recommends that policymakers reform Waqf management and encourage its greater involvement in poverty reduction efforts. By doing so, Waqf could become an essential tool for reducing poverty and improving the socioeconomic status of the Muslim community.